Actividades de pintura basadas en la arteterapia para el desarrollo madurativo de la motricidad fina en los estudiantes de EGB preparatoria de la escuela de educación básica “Nidia Jaramillo” en el período 2021-2022 - Colcha Guaraca, María del Rocío (2022)
ABSTRACT: The objective of this research was to analyze the importance of painting in the maturational development of fine motor skills, we worked with 57 boys and 43 girls, a total of 80 high School students from the Nidia Jaramillo basic education school, with a qualitative approach, basic type design, ethnographic, inductive and field method, the observation sheet used. The maturational level of the children is found in 42.7% in the initiated level which is equivalent to 53 children, in process it is found in 37.09% which is equivalent to 46 children and in acquired it is 20.21% what which is equivalent to 25 children. The importance of students using painting activities were very relevant for the development of fine motor skills, finger painting, sponge painting, cotton swab painting and brush painting. A didactic guide called I am a great Artist designed, which will allow the development of fine motor skills in children, through painting exercises.